T cell epitope engineering: an avian H7N9 influenza vaccine strategy for pandemic preparedness and response. Issue 9 (2nd September 2018) - Moise, Leonard; M. Biron, Bethany; Boyle, Christine M.; Kurt Yilmaz, Nese; Jang, Hyesun; Schiffer, Celia; M. Ross, Ted; Martin, William D.; De Groot, Anne S.
ABSTRACT: The delayed availability of vaccine during the 2009 H1N1 influenza pandemic created a sense of urgency to better prepare for the next influenza pandemic. Advancements in manufacturing technology, speed and capacity have been achieved but vaccine effectiveness remains a significant challenge. Here, we describe a novel vaccine design strategy called immune engineering in the context of H7N9 influenza vaccine development. The approach combines immunoinformatic and structure modeling methods to promote protective antibody responses against H7N9 hemagglutinin (HA) by engineering whole antigens to carry seasonal influenza HA memory CD4 + T cell epitopes – without perturbing native antigen structure – by galvanizing HA-specific memory helper T cells that support sustained antibody development against the native target HA. The premise for this vaccine concept rests on (i) the significance of CD4 + T cell memory to influenza immunity, (ii) the essential role CD4 + T cells play in development of neutralizing antibodies, (iii) linked specificity of HA-derived CD4 + T cell epitopes to antibody responses, (iv) the structural plasticity of HA and (v) an illustration of improved antibody response to a prototype engineered recombinant H7-HA vaccine. Immune engineering can be applied to development of vaccines against pandemic concerns, including avian influenza, as well as other difficult targets.